2019
DOI: 10.3389/fneur.2019.01162
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Method for Identifying Critical Interactions Between Gene Pairs in Alzheimer's Disease Prediction

Abstract: Background: Alzheimer's disease (AD) is the most common type of dementia. Scientists have discovered that the causes of AD may include a combination of genetic, lifestyle, and environmental factors, but the exact cause has not yet been elucidated. Effective strategies to prevent and treat AD therefore remain elusive. The identified genetic causes of AD mainly focus on individual genes, but growing evidence has shown that complex diseases are usually affected by the interaction of genes in a network. Few studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…) and calmodulin-like 3 (CALML3; (Chen et al, 2019)). Even though these results suggested that multiple proteins, or a multiprotein complex, could be ligands of active compound, we focused on MIF because of its known role in infection and neurodegenerative disorders (Petralia et al, 2020).…”
Section: Identification Of Cellular Host Proteins Targeted By Active Compoundmentioning
confidence: 99%
“…) and calmodulin-like 3 (CALML3; (Chen et al, 2019)). Even though these results suggested that multiple proteins, or a multiprotein complex, could be ligands of active compound, we focused on MIF because of its known role in infection and neurodegenerative disorders (Petralia et al, 2020).…”
Section: Identification Of Cellular Host Proteins Targeted By Active Compoundmentioning
confidence: 99%
“…A total of 10 standard algorithms, including support vector machine (SVM), random forest (RF), extra tree, adaptive boosting (AdaBoost), gradient boosting, multilayer perceptron (MLP), K-nearest neighbors (KNN), logistic regression, linear discriminant analysis, and Gaussian Naive Bayes classifier (Gaussian NB), were used in this study. First, we divided the GSE131617 into two parts according to 70% training and 30% testing and selected 10 machine learning algorithms for AD classifiers according to the suggestion of previous studies (Kringel et al, 2018;Tunvirachaisakul et al, 2018;Xu et al, 2018;Chen et al, 2019;Shigemizu et al, 2019;So et al, 2019;Bi et al, 2020;Yaman et al, 2020). Then we optimized the AD classifiers through parameter adjustment and selected 30% of the data as the test.…”
Section: Validation Of Significant Hub Genes By Machine Learningmentioning
confidence: 99%
“…Therefore, predictive analysis of AD at the genetic level is particularly important. Although many scholars have proposed analytical methods in predicting AD, for example, Allen et al 33 and Chen et al, 34 little research integrates different types of genetic data for better prediction of AD. Intuitively, different types of genetic data incorporates more information compared with focusing on only one specific genetic data type.…”
Section: Real Data Analysismentioning
confidence: 99%